Developing Student Character through the Implementation of Deep Learning Management: Lessons from Cianjur Elementary Schools - Nenden Diana; N. Dede Khoeriah (At Turots: Jurnal Pendidikan Islam, 2026)
This study investigated the implementation of deep learning management in fostering students' character within primary school settings, specifically focusing on GR Terry's established four management functions: planning, organizing, actuating, and controlling. Conducted at SDN Sukanagalih 2 and SDN Winayaloka in Cianjur Regency, the research utilized a qualitative approach with a case study methodology. Data collection involved in-depth interviews, participatory observation, and documentation studies, subsequently analyzed using Miles and Huberman's interactive model. The findings indicate a positive trajectory in character development through deep learning management at both institutions; however, persistent challenges were identified across all POAC dimensions. The planning function demonstrated a 65% effectiveness, incorporating character values into lesson plans, yet lacking systematically measurable indicators. The organizing function proved most robust, characterized by efficient task distribution and coordination, though parental engagement remained limited. The actuating function scored 60%, primarily due to inconsistent project-based learning implementation, attributed to time and resource constraints. The controlling function registered the lowest score, as comprehensive character assessment systems were not fully integrated into the school's evaluation processes. Overall, the average implementation level of deep learning management was determined to be 62.5%. This research highlights a disparity between the theoretical ideals of learning management and its practical application in elementary schools, particularly concerning reflection and character evaluation. A key contribution of this study is the integration of the managerial POAC paradigm with a pedagogical deep learning approach focused on character formation, culminating in the conceptual model of Character-Based Deep Learning Management. This model redefines POAC as a reflective, collaborative, and contextual framework for character development, transcending its conventional administrative role. Consequently, this research advances educational management practices in Indonesian primary schools by advocating for impactful and sustainable character education initiatives